Peran Bimbingan dan Konseling dalam Pendidikan Seksual Remaja dalam Novel Kepergian Kedua Karya Amanatia Junda - Anis ameliyasari; Ainy zahra budi syadza; Eva dwi kurniawan (JOURNAL SAINS STUDENT RESEARCH, 2024)
The purpose of this study is to provide information about the importance of sexual education in adolescents. Reflecting on the story of a beautiful character in the novel Kepergian Kedua by Amanatia Junda. The problem raised is the impact of sexual education that is not given, resulting in pregnancy at an immature age without thinking about the readiness of the body. The role of Guidance and Counseling in dealing with this is to provide an understanding of sexual education and the positive impacts that exist in sexual education. In addition to providing information, Guidance and Counseling becomes a safe place for adolescents to talk about problems or questions they have related to sexuality. Informative sexual education will help adolescents make wise decisions about sex and their relationships. In this study, it is hoped that teenagers can now be more self-controlled and think about the consequences of having free sex. The method used is a hermeneutic approach. The results obtained show that sexual education must be given as early as possible for the future of adolescents themselves